2018
DOI: 10.3390/md16120480
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Human Complement System by Antimicrobial Peptide Arenicin-1 from Arenicola marina

Abstract: Antimicrobial peptides from marine invertebrates are known not only to act like cytotoxic agents, but they also can display some additional activities in mammalian organisms. In particular, these peptides can modulate the complement system as was described for tachyplesin, a peptide from the horseshoe crab. In this work, we investigated the influence on complement activation of the antimicrobial peptide arenicin-1 from the marine polychaete Arenicola marina. To study effects of arenicin on complement activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…The earlier results of our investigations confirm the literature data about the interactions between C1q and human defensins, tachyplesin-1, arenicin-1 (Ar-1), protegrin-1 form complexes with C1q directly [6]. We also showed that different AMPs possess modulator activity on complement depending on peptide concentrations; in particular, Ar-1 influenced the classical and alternative complement activation pathways [7].…”
supporting
confidence: 90%
“…The earlier results of our investigations confirm the literature data about the interactions between C1q and human defensins, tachyplesin-1, arenicin-1 (Ar-1), protegrin-1 form complexes with C1q directly [6]. We also showed that different AMPs possess modulator activity on complement depending on peptide concentrations; in particular, Ar-1 influenced the classical and alternative complement activation pathways [7].…”
supporting
confidence: 90%
“…These substances not only participate in host defense against pathogens but they also possess immunomodulatory activity [ 11 ]. In particular, human and non-human AMPs were found to bind complement proteins and to modulate human complement system activity [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Papers included in this Special Issue deal with marine polychaeta, providing good examples of their biological potential. The peptides arenicins and nicomicins, isolated from Arenicola marina [21,22] and Nicomache minor [23], respectively, exhibited in vitro antimicrobial activity and possessed cytotoxicity against cancer cells. Arenicin was shown to modulate the human complement system [22].…”
mentioning
confidence: 99%
“…The peptides arenicins and nicomicins, isolated from Arenicola marina [21,22] and Nicomache minor [23], respectively, exhibited in vitro antimicrobial activity and possessed cytotoxicity against cancer cells. Arenicin was shown to modulate the human complement system [22]. At relatively low concentrations, the peptide stimulates complement activation and lysis of target erythrocytes, whereas at higher concentrations arenicin acts as a complement inhibitor [22].…”
mentioning
confidence: 99%
See 1 more Smart Citation